The Effectiveness of Law Enforcement Against Online Gambling Crimes in the Jurisdiction of the Medan Police Based on the ITE Law and the Criminal Code - Muhammad Hafizullah; Onny Medaline (Yayasan Multidimensi Kreatif, 2026)
Online gambling is a cybercrime that continues to increase in Indonesia, including in the jurisdiction of the Medan Police. Data shows that after experiencing a drastic decline from 40 cases in 2020 to just 5 cases in 2023, online gambling cases surged back to 40 cases in 2024 and peaked in 2025 with 46 cases (a 700% increase from 2023). This study aims to analyze the effectiveness of law enforcement against online gambling crimes based on Article 27 paragraph (2) of the ITE Law and Article 303/303 bis of the Criminal Code in the Medan Police. This study uses an empirical legal research method with a sociological juridical approach through in-depth interviews with investigators, prosecutors, and case document studies for the 2020-2025 period. The data was analyzed using Soerjono Soekanto's theory of legal effectiveness which assessed five factors: legal substance, law enforcement, facilities and facilities, society, and legal culture. The results of the study show that law enforcement has not been optimally effective with an effectiveness rate of around 59% (less effective category). The trend of cases decreasing drastically in 2023 but surging again in 2024-2025 indicates that law enforcement is temporary and has not been able to provide a long-term deterrent effect. Inhibiting factors include: limited competence of investigator human resources in digital forensics (only 30% are certified), lack of digital forensic facilities, regulations that have not been optimal to regulate cross-border jurisdictions, low public legal awareness, and coordination between institutions that has not been maximized. The seasonal pattern shows that the peak of cases occurs in November-December (bonus season and year-end celebrations) with an average of 5.2 cases per month, while the July-August period is the lowest period. Recommendations for increasing effectiveness include: improving regulations, increasing human resource capacity through international certification, procurement of digital forensic tools and building ISO-standard forensic labs, strengthening coordination through inter-agency MoU, and implementing a comprehensive